Gišogenetic Variation in White-Spruce (Picea glauca (Moench) Voss) Trees of Yukon Beringia, Canada - Rodney Arthur Savidge; Xin Yuan; Hartmut Foerster (Forests, 2023)
Gišogenesis, otherwise known as secondary-xylem development, was investigated in an old-growth upland population of white spruce (Picea glauca (Moench) Voss) trees having morphologically diverse crowns and growing on a south slope north of East Fork Creek bordering never-glaciated Yukon Beringia. After tree felling, trunks were segmented into one-metre lengths. In the laboratory, widths of xylem layers were measured across the four cardinal directions at each height, followed by Pearson’s product momentum correlations to evaluate variation in historical gišogenetic vigour within and between trees. Substantial variation was found, and it cannot readily be explained in terms of differences in extrinsic environment. Physiological differences in intrinsic gišogenetic regulation within a genetically diverse population, comprising both refugia and recent recruits, is proposed as a probable explanation, thus emphasizing the individuality of each tree’s internal control over how it responds to the extrinsic environment. Further investigations within Yukon Beringia may yield insight into evolutionary diversification of gišogenesis.